Acidification of intracellular pH in MM tumor cells overcomes resistance to hypoxia-mediated apoptosis in vitro and in vivo - Gastelum, Gilberto; Kraut, Jeffry; Veena, Mysore; Baibussinov, Alisher; Lamb, Christopher; Lyons, Kylee; Chang, Eric Y.; Frost, Patrick (Frontiers in Oncology, 2023)
Introduction Multiple myeloma (MM) is an incurable cancer of malignant plasma cells that engraft in the bone marrow (BM). It is more than likely that the poorly investigated physical parameters of hypoxia and pH in the tumor microenvironment (TME) is critical for MM survival. Here, we explore the effects of a hypoxic environment on pH regulation and its role in MM survival. Methods We used in vitro models of MM, in which the culturing medium was modified to specific pH and pO2 levels and then measured the effects on cell survival that was correlated with changes in intracellular (pHi) and extracellular pH (pHe). In a MM xenograft model, we used PET/CT to study hypoxia-mediated effects on tumor growth. Results Hypoxia-mediated apoptosis of MM cells is correlated with acidic intracellular pHi (less than < 6.6) that is dependent on HIF activity. Using a polyamide HIF responsive element binding compound, a carbonic anhydrase inhibitor (acetazolamide), and an NHE-1 inhibitor (amiloride) acidified the pHi and lead to cell death. In contrast, treatment of cells with an alkalization agent, Na-lactate, rescued these cells by increasing the pHi (pH > 6.6). Finally, treatment of mice with acetazolamide decreased cell growth in the tumor nodules. Discussion Targeting hypoxia and HIF have been proposed as an anti-tumor therapy but the clinical efficacy of such strategies are modest. We propose that targeting the pHi may be more effective at treating cancers within a hypoxic TME.